Market distortions in flexibility markets caused by renewable subsidies: The case for side payments - Jonas Höckner; Simon Voswinkel; Christoph Weber (University of Duisburg-Essen, House of Energy Markets & Finance, 2019)
Strongly increasing costs of congestion management have provoked a discussion in Europe about new approaches to solve grid congestions in a more efficient way. One approach is to design flexibility markets. In this paper we focus on the effects of subsidies for renewable energy on the market outcome of a flexibility market. We show that subsidies can cause market distortions and lead to an inefficient selection of flexibility options to solve grid congestions. We propose the implementation of side payments together with price caps and uniform pricing to achieve an efficient market design. Ultimately choosing between flexibility markets with and without side payments involves a tradeoff between minimizing system costs and maximizing renewable infeed. Our analysis provides the framework for a conscious political choice on that subject.
Keywords: Q41; Q48; 330; congestion management; smart markets; flexibility markets; side payments; renewables